Pengaruh Ekstraksi Benih dengan HCl dan Jenis Wadah Penyimpanan terhadap Daya Simpan Benih Tomat (Lycopersicum esculentum Mill.) - Maheswari, Mea Aprilia; Astawa, I Nyoman Gede; Darmawati, Ida Ayu Putri (Fakultas Pertanian Universitas Udayana, 2024)
Effect of Seeds Extraction with HCl and Types of Storage Packaging on Storability of Tomato Seeds (Lycopersicum esculentum Mill.). This study aims to determine the effect of seeds extraction with HCl and types of storage packaging on storability of tomato seeds (Lycopersicum esculentum Mill.). This study used a factorial Completely Randomized Design with two factors. The first factor was HCl extraction which consists of five levels, namely HCl concentration 0% (K0), 1% (K1), 2% (K2), 3% (K3) and 4% (K4). The second factor was the type of storage packaging which consists of three levels, namely aluminium foil (JA), plastic clip (JP) and glass bottles (JB). Each treatment was repeated 3 times. The research was conducted at the Plant Breeding and Seed Technology Laboratory, Faculty of Agriculture, Udayana University from September-December 2022. The result showed the storage for 12 weeks used HCl extraction 2% in aluminium foil (K2JA) obtained the best average value to maintain the storabilitu of tomato seeds which is indicated by the value of water content (5,04%), germination (86,66%), simultaneous growth (82,22%) and vigor storability (82,22%) compared to another HCl concentration and storage packaging.